THE LANGUAGE LEARNING TASK: CBL (CONTENT BASED LEARNING) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
This study examines Content-Based Learning (CBL) as a strategic approach to language acquisition, exploring its theoretical foundations and practical applications in educational settings. The research analyzes how integrating substantive academic content with language instruction enhances both linguistic competence and subject knowledge acquisition.